2000
DOI: 10.1007/bf02463151
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization of evoked secretion of quanta of mediator as a mechanism facilitating the action of sympathomimetics

Abstract: Experiments on frog neuromuscular junction preparations with extracellular recording of nerve terminal action potentials and single-quantum end-plate currents (EPC) were used to assess the time course of evoked quantum secretion of mediator by analyzing histograms of the distribution of true synaptic delays. These studies showed that noradrenaline, isoproterenol, and dobutamine change the kinetics of secretion of quanta, leading to synchronization of the process of mediator release; substances blocking beta-ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Furthermore, pharmacological stimulation of adrenoceptors in mouse diaphragm muscles affected spontaneous and evoked release of acetylcholine in an adrenoceptor-dependent manner: while agonists of adrenoceptors α 1 and β 1 decreased spontaneous release and quantal content, β 2 -AR stimulation increased quantal content (Tsentsevitsky et al 2020 ). Finally, norepinephrine and β 1 -agonists were found to synchronize evoked potentials in fatigued frog cutaneous pectoris and mouse diaphragm preparations (Bukharaeva et al 2000 ; Tsentsevitsky et al 2020 ). At difference, norepinephrine was not active in mouse soleus muscle, but epinephrine was (Khuzakhmetova and Bukharaeva 2021 ).…”
Section: Experimental Evidence For the Functional Relevance Of Sympat...mentioning
confidence: 99%
“…Furthermore, pharmacological stimulation of adrenoceptors in mouse diaphragm muscles affected spontaneous and evoked release of acetylcholine in an adrenoceptor-dependent manner: while agonists of adrenoceptors α 1 and β 1 decreased spontaneous release and quantal content, β 2 -AR stimulation increased quantal content (Tsentsevitsky et al 2020 ). Finally, norepinephrine and β 1 -agonists were found to synchronize evoked potentials in fatigued frog cutaneous pectoris and mouse diaphragm preparations (Bukharaeva et al 2000 ; Tsentsevitsky et al 2020 ). At difference, norepinephrine was not active in mouse soleus muscle, but epinephrine was (Khuzakhmetova and Bukharaeva 2021 ).…”
Section: Experimental Evidence For the Functional Relevance Of Sympat...mentioning
confidence: 99%
“…The asynchrony of individual quanta secretion is manifested by the dispersion of real synaptic delays of uni-quantal EPPs recorded in low Ca 2+ /high Mg 2+ conditions [ 52 , 55 ] or by a greater increase in the rise time of multi-quantal EPP compared to the MEPP rise time [ 56 , 57 ]. More synchronous release of quanta leads to the EPP amplitude increasing and thus facilitates synaptic transmission [ 58 ] ( Figure 1 ).…”
Section: Sympathomimetic Effects On Ach Quantal Release Evoked By the Nerve Stimulusmentioning
confidence: 99%
“…It was shown that the synchronizing action of noradrenaline leads to an increase in the amplitude of the multiquantal current of the end plate in the “fatigued” muscle and underlies the Orbeli–Ginetsinsky phenomenon—an increase in muscle contractions upon stimulation of the sympathetic nerve [ 6 , 7 ]. Therefore, the synchronization of ACh secretion may be a mechanism for the facilitating action of the sympathomimetics [ 58 ].…”
Section: Sympathomimetic Effects On Ach Quantal Release Evoked By the Nerve Stimulusmentioning
confidence: 99%